Risk and Prognostic Factors for Different Organ Metastasis in Primary Osteosarcoma: A Large Population‐Based Analysis. Issue 4 (16th March 2022) - Xu, Guijun; Wu, Haixiao; Zhang, Yanting; Xu, Yao; Guo, Xu; Baklaushev, Vladimir P.; Chekhonin, Vladimir P.; Peltzer, Karl; Wang, Jun; Lu, Feng; Wang, Guowen; Wang, Xin; et al.
Abstract : Objective: Based on a large public cohort, we aimed to investigate the prevalence of distant metastases in patients with osteosarcoma, to evaluate the survival of patients with different metastases and to reveal the related risk and prognostic factors for distant metastases. Methods: The information of osteosarcoma patients with or without distant metastases was retrospectively extracted from the Surveillance, Epidemiology, and End Result database from January 2010 to December 2015. Patients were excluded if they were diagnosed at autopsy or via death certification. The Kaplan–Meier method was used to calculate the overall survival in the entire cohort and across patients with metastases to different organs. The related prognostic factors were investigated by univariate and multivariate Cox proportional hazard regression analysis. The logistic regression method was used to reveal the risk factors for the development of different metastases. The effects of different variables on the survival and prevalence of distant metastases were compared using subgroup analysis. Variables with P  < 0.05 in the univariate regression analysis were further examined using multivariate regression analysis. Results: In total, 1470 osteosarcoma patients (mean age 30 ± 22 years) were included, among which 278 patients (18.9%) were initially diagnosed with distant metastasis. The median follow‐up duration was 33.0 (30.2–35.8) months. The lung was the most common metastatic site (83.8%), followed by the bone (21.9%), liver (2.9%), and brain (2.2%). A total of 232 patients (83.5%) presented only one distant metastatic site, while the other 46 patients showed two or more metastatic sites. A lower proportion of metastasis was observed in patients aged from 25 to 59 years [odds ratio (OR) = 0.59; 95% confidence interval (CI): 0.37–0.95]. More metastases were noted in patients with T2/T1 (OR = 1.91; 95% CI: 1.28–2.84), T3/T1 (OR = 4.48; 95% CI: 1.78–11.30) and N1/N0 stages (OR = 6.66; 95% CI: 2.68–16.56). The 1‐, 3‐, and 5‐year overall survival rates for metastatic patients were 57.3% (95% CI: 50.8%–63.8%), 25.3% (95% CI: 18.8%–31.9%), and 18.1% (95% CI: 10.2%–26.0%), respectively. Metastatic patients older than 25 years were prone to have poor survival and a relatively better prognosis (hazard ratio = 0.41; 95% CI: 0.25–0.69) was noticed among those who underwent surgery on the primary site. Different metastatic organs have homogeneous and heterogeneous risk and prognostic factors. Conclusion: The high incidence of initial distant metastasis in osteosarcoma and the inconsistent predictive factors should be given more attention in the clinical management of patients with osteosarcoma. Abstract : Homogenous and heterogenous risk and prognostic factors were noticed for osteosarcoma patients with distant metastasis to different organs, which can potentially guide organ‐specific distant metastasis screening and management.